Career education an overview with special focus on the agricultural sector - Gabriel, Rhodelia L. (Education quarterly.)
The concept of career education represents one attempt to improve our educational system to better meet the educational needs of all students. Career education is a comprehensive effort to integrate concepts into the existing curriculum of our educational system. At present, the concept of career education can be said to be in a developing stage.Clearly, further development of this concept is needed. The specific means for implementing this concept in Philippine education remains largely undeveloped.